Preliminary Use of Indocyanine Green Fluorescence Angiography and Value in Predicting the Vascular Supply of Tissues Needed to Perform Cloacal, Anorectal Malformation, and Hirschsprung Reconstructions - Rentea, Rebecca Maria; Halleran, Devin R.; Ahmad, Hira; Sanchez, Alejandra Vilanova; Gasior, Alessandra C.; McCracken, Katherine; Hewitt, Geri D.; Alexander, Victoria; Smith, Caitlin; Weaver, Laura; Wood, Richard J.; Levitt, Marc A. (European Journal of Pediatric Surgery, 2019)
Introduction Reconstructive techniques for cloaca, anorectal malformations (ARM), and Hirschsprung disease (HD) may require intestinal flaps on vascular pedicles for vaginal reconstruction and/or colonic pull-throughs. Visual assessment of tissue perfusion is typically the only modality used. We investigated the utility of intraoperative indocyanine green fluorescence angiography (ICG-FA) and hypothesized that it would be more accurate than the surgeon's eye.Materials and Methods Thirteen consecutive patients undergoing cloacal reconstruction (9), HD (3), and ARM repair (1) underwent ICG-FA laser SPY imaging to assess colonic, rectal, vaginal, and neovaginal tissue perfusion following intraoperative visual clinical assessment. Operative findings were correlated with healing at 6 weeks, 3 months, and 1 year postoperatively.Results ICG-FA resulted in a change in the operative plan in 4 of the 13 (31%) cases. In three cases, ICG-FA resulted in the distal bowel being transected at a level (>10 cm) higher than originally planned, and in one case the distal bowel was discarded, and the colostomy used for pull-through.Conclusion ICG-FA correctly identified patients who might have developed a complication from poor tissue perfusion. Employing this technology to assess rectal or neovaginal pull-throughs in cloacal reconstructions, complex HD, and ARM cases may be a valuable technology.
Keywords: indocyanine green fluorescence angiography; cloaca; Hirschsprung disease; fluorescence angiography; anorectal malformation